Experimental Study Of Soil As Porous Medium For Evaporative Cooling - Ganesan, Lagunesvary (2019)
Cooling is becoming a major concern nowadays due to the increment of ambient temperature. Soil is vastly used in passive and partially passive evaporative cooling systems. Roof cooling, heat pipe, Zeer pot and more applications were built to use soil as porous medium in inducing and preserving cooling. However, there are no many literatures to justify the influence of physical property of soil on evaporative cooling. Evaporative cooling influenced by the air humidity, air flow rate, presence of water, heat energy availability and the physical properties of porous medium. Loam soil, sand, gravel and small rocks were studied as a porous medium in an evaporative cooling system. Variation in particle size influences soil porosity and permeability. The loam soil, sand, gravel and small rocks provided 23.8%, 34.7%, 51.3% and 64.8% porosity, while 0.02 ml/s, 0.43 ml/s, 9.77 ml/s and 12.37 ml/s permeability respectively. Porosity and permeability influences air and water flow inside the porous medium. A compact porous medium feasible to sustain coldness generated for period of time. The research was continued with 1 bar to 5 bar compressed air to study the influence of loam soil, sand, gravel and small rocks on evaporative cooling. The setup with 5 bar compressed air performed better due to its low relative humidity and high volumetric density. Loam soil and sand were worked greatly in 30% moisture content while gravels and small rocks were able to work with 5% water content due to its physical characteristics. In a comparative experiment with 10 kg soil and 30% moisture content, the loam soil archived minimum temperatures of 16.43°C while sand, gravel, and small rocks were 17.06°C, 17.40°C, and 18.26°C respectively. The water lost from 2 hours of evaporation in loam soil, sand, gravel and small rocks are 0.3 kg, 0.35 kg, 0.45 kg and 0.45 kg respectively. Higher water lost through evaporation results higher heat lost. While the cooling rates reduces from 0.103°C/min, 0.098°C/min, 0.098°C/min, 0.096°C/min and 0.084°C/min for gravels, water, small rocks, loam soil and sand. However, selection of the type of soil for an evaporation cooling system is based on the requirement of the application. Loam soil and sand are the great selection for an application that required cooling effect, thermal sustainability, and stability. While gravels and small rocks are good for an application that required a high rate of evaporation.